Survival and detection of SARS-CoV-2 variants on dry swabs post storage - Gordhan, Bhavna G.; Ealand, Christopher S.; Kana, Bavesh D. (Frontiers in Cellular and Infection Microbiology, 2022)
COVID-19 has resulted in nearly 598 million infections and over 6.46 million deaths since the start of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic in 2019. The rapid onset of the pandemic, combined with the emergence of viral variants, crippled many health systems particularly from the perspective of coping with massive diagnostic loads. Shortages of diagnostic kits and capacity forced laboratories to store clinical samples resulting in huge backlogs, the effects of this on diagnostic pickup have not been fully understood. Herein, we investigated the impact of storing SARS-CoV-2 inoculated dry swabs on the detection and viability of four viral strains over a period of 7 days. Viral load, as detected by qRT-PCR, displayed no significant degradation during this time for all viral loads tested. In contrast, there was a ca. 2 log reduction in viral viability as measured by the tissue culture infectious dose (TCID) assay, with 1-3 log viable virus detected on dry swabs after 7 days. When swabs were coated with 102 viral copies of the Omicron variant, no viable virus was detected after 24 hours following storage at 4°C or room temperature. However there was no loss of PCR signal over 7 days. All four strains showed comparable growth kinetics and survival when cultured in Vero E6 cells. Our data provide information on the viability of SARS-CoV-2 on stored swabs in a clinical setting with important implications for diagnostic pickup and laboratory processing protocols. Survival after 7 days of SARS-CoV-2 strains on swabs with high viral loads may impact public health and biosafety practices in diagnostic laboratories.